Phytocenotic characteristics of the vegetation cover of avalanche paths in Central Altai - Petr A. Kosachev; Nikolay I. Bykov; Madina E. Kulushpaeva; Natalia V. Ovcharova (Acta Biologica Sibirica, 2025)
The article presents the characteristics of plant cenoses in the studied avalanche paths of Central Altai (Aigulaksky, Kuraisky, Listvyaga, North Chuisky Ridges). They were analyzed using the Juss 7.0 software package and divided into 2 main groups: forest and shrub-herbaceous. The forest group includes 8 cenoses with 130 plant species; shrub-herbaceous one includes 16 communities with 205 species. Forest cenoses divided into 2 groups, and shrub-herbaceous – into 3 groups, classified on the basis of diagnostic species, characteristics of tree, shrub and herb layers, as well as the coenoflora core. All the groups of communities, both forest and shrub-herbaceous, according to the geobotanical zoning of G.N. Ogureeva (1980), correspond to two geobotanical districts and regions of Central Altai highland- taiga-forest-steppe province: 1) Kholzunsko-Korgonsky highland-taiga district and Verkhnekatunsky highland-taiga-forest-steppe region (Listvyaga Ridge); 2) Chuisko-Argutsky nival-highland-taiga-forest-steppe district and Chuisko-Argutsky taiga-forest-steppe region (Aigulaksky, Kuraisky, North Chuisky Ridges). Considering the shrub-herbaceous vegetation of the studied avalanche paths of Central Altai, it is possible to assume their annual avalanche activity. In some avalanche paths, the type of avalanche, the time of a catastrophic avalanche, and the approximate last year of a powerful avalanche were estimated.